Unit Cost Analysis In Heart Failure Inpatients Using The Time Driven Activity Based Costing Method At Type D Hospital In Sragen - Nadhiasari, Aulia; Pribadi, Firman; Nazaruddin, Ietje (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Heart failure is one of the most common non-communicable diseases in adults. The number of cases of patients admitted to hospitals due to heart failure is quite large, resulting in a high frequency of hospitalizations and high patient treatment costs. Cost calculation is very important for health care providers in order to conduct financial evaluations. One way to calculate costs in hospitals is to use unit cost analysis. The purpose of the study was to determine the unit cost of treatment for heart failure patients in inpatient settings, especially in Type D hospitals in Sragen. Subjects and Method: This study is a qualitative type study using a case study approach to unit cost to calculate the inpatient treatment rate of patients with chronic heart failure using the Time Driven Activity Based Costing method. Furthermore, the difference with the INA CBGs rate is seen. There are two sources of data in this study, namely primary data from interview results from sources directly in the field and secondary data from financial report data and clinical pathway data for inpatient services for patients with chronic heart failure in hospitals. Results: The unit cost of treatment of heart failure patients in the inpatient installation using the Time Driven Activity Based Costing method at type D hospitals in Sragen amounted to Rp 2,186,089. The difference in heart failure treatment costs in the type D hospital inpatient installation in Sragen using the Time Driven Activity Based Costing method with the patient treatment rate based on INA-CBG'S is Rp 250,211 (10%). Conclusion: The unit cost of treatment of heart failure patients in the inpatient installation using the Time Driven Activity Based Costing method is Rp 2,186,089